2006
DOI: 10.1111/j.1468-2982.2006.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Premonitory and Resolution Symptoms in Migraine: A Prospective Study in 100 Unselected Patients

Abstract: The nosology of migraine premonitory (PS) and resolution (RS) symptoms was studied in 100 migraineurs consulting their general physician. They were asked to fill in, for three attacks, a PS and RS questionnaire. 'True' PS/RS were those experienced the day before (or the day after) the headache had started only if they were not present in a questionnaire completed in a pain-free period. True PS and RS were experienced by 84% and 80%, respectively, of subjects for the first attack. The mean and range (per patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
181
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(204 citation statements)
references
References 22 publications
16
181
4
1
Order By: Relevance
“…Two authors (SG and GB) read the title and abstract of every identified study and critically appraised the full text of potentially eligible studies. Table 1 summarizes the studies of prodrome reported in children and adults with migraines [4][5][6][7][8][9][10][11]. Our search reveals no devoted studies to the diagnostic and therapeutic significance of preictal symptomatology in migraines.…”
Section: Methods Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Two authors (SG and GB) read the title and abstract of every identified study and critically appraised the full text of potentially eligible studies. Table 1 summarizes the studies of prodrome reported in children and adults with migraines [4][5][6][7][8][9][10][11]. Our search reveals no devoted studies to the diagnostic and therapeutic significance of preictal symptomatology in migraines.…”
Section: Methods Literature Searchmentioning
confidence: 99%
“…It shows the prevalence of prodromal symptoms in children and adults with migraine with and without aura [4][5][6][7][8][9][10][11][12]. …”
Section: Postictal Symptommentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] In addition, the majority of the studies performed so far have only looked at symptoms starting before the prevalence rates of 9-88%. 3,[8][9][10][11][12][13][14][15][16][17][18] See Table 1 for a breakdown of studies to date in the literature looking at premonitory symptom prevalence.…”
Section: Prevalence Of Premonitory-like Symptoms In Migrainementioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] The most common symptoms seem to be fatigue (see red in Table 1), mood change (see blue in Table 1) and yawning (see green in Table 1). These are consistent across the studies.…”
Section: Phenotype Of Premonitory-like Symptomsmentioning
confidence: 99%